The Resource Dependence Role of Corporate Directors: Strategic Adaptation of Board Composition in Response to Environmental Change - Hillman, Amy J.; Cannella, Albert A.; Paetzold, Ramona L. (Journal of Management Studies, 2000)
Most research on corporate directors has focused on two roles: agency and resource dependence. While these two roles are theoretically and practically distinct, previous research has used the same classification scheme for measuring board composition regardless of role examined. Our paper examines the resource dependence role of directors and posits that the widely used insider/outsider categorizations do not adequately capture this role of directors. A taxonomy of directors is presented specifically for studying the resource dependence role. We then apply the taxonomy to a sample of US airline firms undergoing deregulation, and examine how board composition changes parallel the changing resource dependence needs of the firms. We conclude that the board’s function as a link to the external environment is an important one, and that firms respond to significant changes in their external environment by altering board composition.